Petrogenesis of ore-bearing porphyries from the Duolong porphyry Cu-Au deposit, central Tibet: Evidence from U-Pb geochronology, petrochemistry and Sr-Nd-Hf-O isotope characteristics - Li, J.; Qin, K.; Li, G.; Xiao, B.; Zhao, J.; Cao, Mingjian; Chen, L. (Elsevier BV, 2013)
The Duolong porphyry Cu-Au deposit (5.4Mt at 0.72% Cu, 41t at 0.23g/t Au), which is related to the granodiorite porphyry and the quartz-diorite porphyry from the Bangongco copper belt in central Tibet, formed in a continental arc setting. Here, we present the zircon U-Pb ages, geochemical whole-rock, Sr-Nd whole-rock and zircon in-situ Hf-O isotopic data for the Duolong porphyries. Secondary ion mass spectrometry (SIMS) zircon U-Pb analyses for six samples yielded consistent ages of ~118Ma, indicating a Cretaceous formation age. The Duolong porphyries (SiO2 of 58.81-68.81wt.%, K2O of 2.90-5.17wt.%) belong to the high-K calc-alkaline series. They show light rare earth element (LREE)-enriched distribution patterns with (La/Yb)N=6.1-11.7, enrichment in large ion lithophile elements (e.g., Cs, Rb, and Ba) and depletion of high field strength elements (e.g., Nb), with negative Ti anomalies. All zircons from the Duolong porphyries share relatively similar Hf-O isotopic compositions (d18O=5.88-7.27-; eHf(t)=3.6-7.3), indicating that they crystallized from a series of cogenetic melts with various degrees of fractional crystallization. This, along with the general absence of older inherited zircons, rules out significant crustal contamination during zircon growth. The zircons are mostly enriched in d18O relative to mantle values, indicating the involvement of an 18O-enriched crustal source in the generation of the Duolong porphyries. Together with the presence of syn-mineralization basaltic andesite, the mixing between silicic melts derived from the lower crust and evolved H2O-rich mafic melts derived from the metasomatized mantle wedge, followed by subsequent fractional crystallization (FC) and minor crustal contamination in the shallow crust, could well explain the petrogenesis of the Duolong porphyries. Significantly, the hybrid melts possibly inherited the arc magma characteristics of abundant F, Cl, Cu, and Au elements and high oxidation state, which contributed to the formation of the Duolong porphyry Cu-Au deposit. © 2013 Elsevier B.V..